2017
DOI: 10.1007/s10143-017-0913-1
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and silent cerebral infarction following surgical clipping of unruptured intracranial aneurysms: incidence, risk factors, and clinical outcome

Abstract: Cerebral infarction (CI) associated with clipping of unruptured intracranial aneurysms (UIAs) has not been completely studied. The role of individual and operative characteristics is not known, and the risk of silent CI has not been well described. To determine the incidence, risk factors, and clinical outcome of postoperative CI, we retrospectively analyzed 388 consecutive patients undergoing clipping of UIAs between January 2012 and December 2015. We reviewed the pre- and postoperative computed tomography (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
3
13
1
Order By: Relevance
“…Zhang et al's study showed that invasive surgical approach, intraoperative monitoring, effective management of cerebrovascular perfusion, and coagulation can prevent the development of cerebral ischemia and aneurysm rupture. [ 11 ] However, manipulation of the intrasaccular thrombus during coiling can lead to further embolization, [ 12 ] given the risk of intraoperative thromboembolic events, it is possible that the risk of surgery in these patients is higher than in patients with asymptomatic UIA. Further studies are needed before this option can be widely implemented in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al's study showed that invasive surgical approach, intraoperative monitoring, effective management of cerebrovascular perfusion, and coagulation can prevent the development of cerebral ischemia and aneurysm rupture. [ 11 ] However, manipulation of the intrasaccular thrombus during coiling can lead to further embolization, [ 12 ] given the risk of intraoperative thromboembolic events, it is possible that the risk of surgery in these patients is higher than in patients with asymptomatic UIA. Further studies are needed before this option can be widely implemented in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, aneurysms grow more easily. In case of blocking or injury of fPCA, infarction develops and patients tend to suffer from poor outcomes because of the lack of compensatory from posterior cerebral circulation [20]. Cerebral infarction is strongly correlated with angiographic vasospasm for ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic complications may also arise from improper clip placement or due to thromboembolism from the aneurysm. The type and severity of neurological consequences depend mostly on the location of the aneurysm [150][151][152][153]. The most frequent type of postoperative events and possibly even underestimated, ischemia leads to poorer outcomes at discharge and often entails a reintervention [153,154].…”
Section: Complications Of Surgical Clippingmentioning
confidence: 99%
“…The type and severity of neurological consequences depend mostly on the location of the aneurysm [150][151][152][153]. The most frequent type of postoperative events and possibly even underestimated, ischemia leads to poorer outcomes at discharge and often entails a reintervention [153,154]. After clipping of UIAs, transcranial Doppler studies show a decrease in transient reduction in cerebrovascular reactivity on the side of the aneurysm, leading to a proneness toward cerebral ischemia [155].…”
Section: Complications Of Surgical Clippingmentioning
confidence: 99%
See 1 more Smart Citation